The Influence of School-Based Management and Teacher's Professionalism toward Teacher’s Performance - Rohma, Siti; Harapan, Edi; Wardiah, Dessy (Journal of Social Work and Science Education, 2020)
This study determined the influence of school-based management and teacher professionalism both partially and simultaneously on the performance of teachers of State Junior High Schools in Prabumulih Timur, Indonesia. The sample of this study were 135 civil servant teachers. Research data collection techniques 1) questionnaire; 2) documentation; and 3) observation. The research data analysis technique used the SPSS for Windows 21. The results of this study indicate that: 1) there is a significant influence of school-based management on the performance of state junior high school teachers in the District of Prabumulih Timur, Prabumulih City; 2) there is a significant influence of teacher professionalism on the performance of teachers of SMP Negeri in the District of Prabumulih Timur, Prabumulih City; 3) there is a significant influence of school-based management and teacher professionalism together on the performance of teachers of SMP Negeri in Prabumulih Timur, Indonesia.